Strategi Penyaluran Pembiayaan Sektor Konstruksi di Bank NTB Syariah - Siti Hudaniyah; Musawar Musawar; Zainuddin Mansyur (Universitas Bumigora, 2023)
In channeling financing to the construction sector at Bank NTB Syariah there are challenges and risks faced in its implementation, including because the project being financed cannot be completed on time, there are delays in payment or the project is not paid, construction activities are delayed due to the transmission rate of the Covid-19 virus . This study aims to determine the strategy of Bank NTB Syariah in channeling financing to the construction sector in dealing with existing challenges and risks. This study uses a qualitative descriptive research method which aims to explain the strategy of Bank NTB Syariah in increasing financing growth in the construction sector with challenges and risks. The sampling technique used in this study was snowball sampling, namely key informants would appoint people who knew the problem to be studied, the data collection technique used by researchers was to conduct in-depth interviews with all informants which were then documented in the form of sound recordings, personal notes, photos, and videos, the results of interviews with informants were then analyzed and explained. The results of the study explain that in implementing the distribution of financing to the construction sector at Bank NTB Syariah it is given to construction business actors/contractors who have project contracts whose funds are sourced from the government/private budget with the aim of infrastructure development projects, financing using musyarakah contracts, Bank NTB strategy Sharia in channeling construction sector financing by conducting in-depth analysis with several stages of the process, as well as mitigating risks in dealing with existing challenges and risks.